MANFAAT HASIL BELAJAR MEMBUAT POLA DI ATAS KAIN SEBAGAI KESIAPAN KERJA DI TAILORING - Nindy Agustina; Astuti Astuti (Fesyen Perspektif, 2016)
The research renewing benefits of learning result makes a pattern on the fabric as ready worl in tailoring. This researchaimed of the study about making a pattern on the fabric that residents learn have knowledge of competence, skills, and work attitude required to make pattern on the fabric in tailoring bussiness. The research  used descriptive analitik method. Study population that course participants LPK Pelita Busana level 2 amount to 25 person and has been studied to make a patteren on the fabrics. Data accumulation such a questionnaires. The result of the study showed more than half residents learn already know the competence to make a pattern on the fabrics according to the steps of making a pattern as ready work in tailoring.Suggestion that the authors propose can be provide benefit to the parties concerned, are to coure participats LPK Pelita Busana expected to develop and improve insight, attitude, and skills, until to improve the quality of manufacture of the pattern on the fabrics to be ready to apply knowledge and skills to working in tailoring